The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/es3051197
|View full text |Cite
|
Sign up to set email alerts
|

Prevented Mortality and Greenhouse Gas Emissions from Historical and Projected Nuclear Power

Abstract: In the aftermath of the March 2011 accident at Japan's Fukushima Daiichi nuclear power plant, the future contribution of nuclear power to the global energy supply has become somewhat uncertain. Because nuclear power is an abundant, low-carbon source of base-load power, it could make a large contribution to mitigation of global climate change and air pollution. Using historical production data, we calculate that global nuclear power has prevented an average of 1.84 million air pollution-related deaths and 64 gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(136 citation statements)
references
References 20 publications
4
121
0
1
Order By: Relevance
“…We selected the cost and sustainability indicators for the MCDMA carefully based on the guidelines of the International Atomic Energy Agency in cooperation with the United Nations Department of Economic and Social Affairs (UNDESA), the International Energy Agency (IEA), Eurostat and the European Environment Agency (EEA) [37], which are relevant to the context of Australia. These were: (1) levelized cost of electricity (which is the minimum cost of electricity at which an electricity producer can sell and still secure an economic return), including carbon pricing between 2013 ($23 tonne CO 2 -e À1 ) and 2050 ($140 tonne CO 2 -e À1 ) [24], and additional costs [31], (2) greenhouse-gas emissions [38], (3) air pollutants Australian Academy of Technological Sciences and Engineering, 2009 [22,[39][40][41][42][43][44][45][46][47][48], (4) land transformation [39,46,[49][50][51][52][53], (5) freshwater consumption [41,48,50,[54][55][56][57][58][59], (6) safety costs [21,60,61] (the probability of severe accidents and the impact of them), (7) solid-waste generation [41,48,[62][63][64][65]…”
Section: Multi-criteria Decision-making Analysismentioning
confidence: 99%
“…We selected the cost and sustainability indicators for the MCDMA carefully based on the guidelines of the International Atomic Energy Agency in cooperation with the United Nations Department of Economic and Social Affairs (UNDESA), the International Energy Agency (IEA), Eurostat and the European Environment Agency (EEA) [37], which are relevant to the context of Australia. These were: (1) levelized cost of electricity (which is the minimum cost of electricity at which an electricity producer can sell and still secure an economic return), including carbon pricing between 2013 ($23 tonne CO 2 -e À1 ) and 2050 ($140 tonne CO 2 -e À1 ) [24], and additional costs [31], (2) greenhouse-gas emissions [38], (3) air pollutants Australian Academy of Technological Sciences and Engineering, 2009 [22,[39][40][41][42][43][44][45][46][47][48], (4) land transformation [39,46,[49][50][51][52][53], (5) freshwater consumption [41,48,50,[54][55][56][57][58][59], (6) safety costs [21,60,61] (the probability of severe accidents and the impact of them), (7) solid-waste generation [41,48,[62][63][64][65]…”
Section: Multi-criteria Decision-making Analysismentioning
confidence: 99%
“…As oil price hikes and instability of nuclear power plants have persisted recently, the volume of coal in use has been on a constant rise due to a relatively smooth supply and fewer problems arising from its use [1,2]. However, the continued use of coal in coal-fired power plants for energy generation will constantly increase the emissions of carbon dioxide and other pollutants and ultimately accelerate global warming [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous scientific comparisons have shown that nuclear fission is among the energy sources that are least polluting and have the lowest overall environmental impact [10]. Operating nuclear power plants do not produce air pollution nor do they emit CO 2 .…”
Section: Nuclear Energy From Fission Has a Low Environmental Impactmentioning
confidence: 99%